The representation of gender, love family and sexuality in the canonical and non-canonical novels of the early republican period - Ural, Tülin. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2001., 2001)
In the conclusion of thesis, it is observed that the authors of both the canonical and non-canonical novels prefer to discuss modernity through using gender and related themes. Moreover, namus (sexual honor) and nationalism form the limits of alternative discourses. Thee is also another big difference between the non-canonical and canonical novels in terms of modernity: the canonical novels explicitly criticize a definition of modernity as a process that increases the possibilities for individual liberation, perceives it as reflection of selfish individualism and defends rather a model of modernity based on more rationally and centrally controlled society. According to the canonical novels, the first model of modernity shows is darker side in woman's degeneration. The fundamental sign of this degeneration is that woman loses her sexual namus. Thus, in the canonical novels, although there are few examples that perceive woman from a positive point of view, the degenerating influence of modernity remains the secret basis on which the story is built. The main question of the canonical novel is a negative one: How should not we modernize? It is a question that reminds the reader primarily of the dangers of modernity. In this study, the defensive position of the canonical novels towards modernization is explained by the tension between nationalism and modernism, in Kemalist ideology and practice (as is the case in many other nation-building process, too.) National identity requires the construction of certain essential characteristics for the nation, peculiar itself. Whereas modernization, especially a project that explicitly declares that it is based on a western model, has to refer to universal values and include elements from the "other". This tension is solved in these novels by suggesting a modernization model "peculiar to Turks". In this process, the critical point is the fact that national uniqueness as difference is defined through the purity of the female body, which is manifested primarily in the protection of her namus.
Keywords: Family in literature.; Sex in literature.; Literature and society.